Development of PLTS Trainers as Learning Media in the Energy Conversion Laboratory - Alensyah, Ardo; Nehru, Nehru; Manab, Abdul; Hais, Yosi Riduas; Tessal, Dasrinal; Kurniawan, Wawan (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Enhancing the quality of learning is worthy by the availability of PLTS trainers. This work intends to build and create PLTS trainers as learning material for renewable energy generation. The preparation of this study was divided into two stages: first, a PLTS media trainer kit and a practical training module that functioned as a handbook for using the media trainer were created. The ADDIE method is used as the development model for the practical guiding module and media trainer. Based on the data analysis findings show that the 10Wp solar module can provide a maximum energy of 5.11Wp for 11 hours when charging a 7.5Ah battery. With a 63 Watt total load, the PLTS trainer's Ah battery can run for 37 minutes. With an average percentage of 93% and 92%, respectively, the material expert validator and media expert have deemed the media trainer and practicum instruction module feasible. This places them in the very good category